The effects of conjugated linoleic acid supplementation on inflammatory cytokines and adipokines in adults: A GRADE-assessed systematic review and dose–response meta-analysis - Rastgoo, Samira; Shimi, Ghazaleh; Shiraseb, Farideh; Karbasi, Ashkan; Ashtary-Larky, Damoon; Yousefi, Mohsen; Golalipour, Elnaz; Asbaghi, Omid; Zamani, Mohammad (Frontiers in Immunology, 2023)
Background and aims Many studies have investigated the effect of conjugated linoleic acid (CLA) supplementation on inflammatory cytokines and adipokines. However, the results of these studies are not consistent. Therefore, this systematic review and meta-analysis were designed to comprehensively evaluate the effect of CLA supplementation on inflammatory cytokines and adipokines. Methods Randomized controlled trials (RCTs) examining the effects of CLA supplementation on C-reactive protein (CRP), interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-α), adiponectin, and leptin, published up to March 2022, were identified through PubMed, SCOPUS, and ISI Web of Science databases. A random-effects model was used to calculate weighted mean differences (WMDs) with 95% confidence intervals (CI) for 42 studies that included 1,109 participants. Results Findings from 42 studies with 58 arms indicated that CLA supplementation significantly decreased IL-6 and TNF-α levels and also slightly increased CRP levels. However, adiponectin and leptin levels did not change after CLA supplementation. A subgroup analysis found that CLA supplementation reduced adiponectin and leptin in women. Conclusion Our results demonstrated that CLA supplementation increased CRP levels and decreased TNF-α and IL-6 levels. Therefore, it seems that CLA can have both proinflammatory and anti-inflammatory roles. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier (CRD42022331110).